Oxford handbook of the British sermon: 1689 - 1901 - Francis, Keith A. (Oxford University Press, 2012)
This handbook accesses historical, theological, rhetorical literary and linguistic studies to demonstrate the interdisciplinary strength of the field of sermon studies and to show the centrality of sermons to private and public life in this 'golden age' of the British sermon.